Enhancement of polyaniline properties by different polymerization temperatures in hydrazine detection - Sambasevam, K.P.; Mohamad, S.; Phang, Sook Wai (Wiley, 2015)
In this study, a simple and cost effective chemical sensor for hydrazine detection was developed using polyaniline (PAni). PAni was synthesized via chemical oxidative method at different polymerization temperatures (-10, -5, 0, and 25 degrees C) in the presence of sodium dioctyl sulfosuccinate (AOT) as dopant. The effect of polymerization temperature on the performance of the PAni sensor for hydrazine detection was evaluated. The sensor response was analyzed using UV-Vis spectrometer, where there is notable decrease in polaron peak at approximate to 780 nm after the PAni was exposed to hydrazine. The reduction in the polaron peak is attributed to the decrease in the conductivity of PAni thin films owing to dedoping process by hydrazine. Fourier transform infrared analysis was carried out to study the intensity ratio of quinoid/benzenoid peak to identify the changes in chemical structure of PAni upon exposure to hydrazine. Besides that, all PAni sensors synthesized at different polymerization temperatures showed good reusability up to 10 cycles with respond and recovery time of 0.12 min and 0.08 min, respectively. Data collected in this study indicate that PAni which was synthesized at -5 degrees C could act as sensitive sensor for hydrazine detection with a detection limit of 0.24 ppm. (c) 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41746.